EVALUATION OF THE IMPLEMENTATION OF GOOD MANUFACTURING PRACTICES (GMP) AT PT XYZ UNIT CENGKARENG - Nahda, Jihan; Fitriani, Aprilia (Jurnal Pangan dan Agroindustri, 2023)
The airline catering industry faces challenges in providing food due to diverse requirements and constrained space and resources on airplanes. This research investigates the application of Good Manufacturing Practices (GMP) in aviation catering production, exploring its potential to enhance product quality, adhere to safety and health standards, and satisfy customer expectations. The research methods employed encompassed observation, interviews, and a thorough examination of credible literature sources.The overall GMP implementation at PT XYZ demonstrated 93.59% compliance and 6.41% non-compliance. In conclusion, the adoption of GMP in aviation catering leads to enhanced product quality and compliance with health standards. Through this approach, airline catering companies can ensure that their products meet both customer quality expectations and health regulations.